Quality evaluation of Coconut Based Snack during storage period - Sivasakthi, M.; Sangeetha, Narayanasamy (International Journal of Scientific Research in Biological Sciences, 2019)
Natural versatile ingredients packed with potent nutrients such as beet root, carrot, ginger and mint have been selected for the recent study for their variable vast phenolic compounds and other functional properties as osmotic infusions in the form of filtrates. Sliced samples (0.8±0.1mm) of matured coconuts were subjected to the process osmotic dehydration from 0 min to 720 min at room temperature. Then the slices were dried in a hot-air oven at temperature 45-60°C for about 6-7 hours and freeze drying at temperature (-40 to 30°C) for a period of 14-16 hours. Osmotic medium without the infusion of filtrates of functional ingredients serves as the control. The snack samples were packed using Aluminium foil laminated LDPE pouches with infusion of 100% nitrogen gas composition and stored at ambient temperature till analyzing the shelf life features like free fatty acids, peroxide value, total sugars, moisture content and microbial growth and the results were interpreted using SPSS tool t test (p≤0.05). Upon three months of storage study, the products quality remained good, where as slight deterioration of shelf life characteristics seen beyond three months, showed the keeping quality of the snack.